High Performance AC Drives Modelling Analysis and Control - Ahmad, Mukhtar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book presents a comprehensive view of high performance ac drives. It may be considered as both a text book for graduate students and as an up-to-date monograph. It may also be used by R & D professionals involved in the improvement of performance of drives in the industries. The book will also be beneficial to the researchers pursuing work on multiphase drives as well as sensorless and direct torque control of electric drives since up-to date references in these topics are provided. It will also provide few examples of modeling, analysis and control of electric drives using MATLAB/SIMULINK.
Modeling of Induction and Synchronous Machines -- Vector Control of Induction Motor Drives -- Direct Torque Control and Sensor-Less Control of Induction Machine -- Control of Permanent Magnet Machine (PM) -- Switched Reluctance Motor Drives (SRM) -- Control of Multiphase AC Motor Drives -- Fuzzy Logic and Neural Network Applications in AC Drives.
Keywords: Engineering; Electronics; Production of electric energy or power; Electric engineering; Engineering; Power Electronics, Electrical Machines and Networks; Energy Technology; Control, Robotics, Mechatronics; Electronics and Microelectronics, Instrumentation